Avaliação de retinopatia da prematuridade em recém-nascidos prematuros acompanhados em serviço de seguimento no Paraná - Pastro, Joziana (2018)
Retinopathy of prematurity (ROP) is a vasoproliferative disease, related to blindness, in Premature Newborns (PN) who, within other factors, used oxygen during hospitalization. Early visual follow-up of preterm newborns by ophthalmologists makes it possible to identify the stage and grade of the disease and the indication of treatment or attendance of its evolution. Nursing orientation is essential to the PN relatives, since ROP is not an easily seen disease, so, parents being aware that the ophthalmologic follow-up is of vital importance for the visual recovery of the baby will make a difference in the child future visual health. Therefore, this study aims to evaluate the prevalence and evolution of ROP in PN, hospitalized in a Neonatal Intensive Care Unit (NICU) and attended at a referral ophthalmologic follow-up service. This is a quantitative, descriptive and exploratory study, carried out in the city of Cascavel. Data collection was done in medical records of PN, born between January 2014 and June 2016, hospitalized in the NICU of the West Paraná University hospital, and followed by the outpatient clinic of Cascavel Eyes Hospital, totaling 181 charts. A quantitative analysis was performed through descriptive and inferential statistic. The prevalence of ROP was 11.31% (n = 50). Relating its characteristics to evolution, the diagnoses prevalent in the PN of the study were respiratory diseases (41.99%) and among comorbidities, sepsis prevailed (63.54%). 80 PN required blood transfusion (44,20%) and 152 (83.98%) used oxygen therapy, with a predominance of mask device (n = 141; 77,90%) and orotracheal tube - TOT (n = 100; 55.25%), on average for 15 days. The highest concentration recorded was hood (45.0%). The time of use and the O2 concentration of TOT, time of mask use and time and concentration of O2 of Continuous Positive Airway Pressure (CPAP), were significant to trigger ROP. Among ROP cases, ten (5.5%) children had severe ROP and required laser treatment. All the PN diagnosed with ROP used oxygen. ROP prevailed in moderate preterm newborns (44%), with ROP grade 3 being the most severe, affecting both extreme and moderate PN. Respiratory diseases, sepsis and procedures such as blood transfusion and oxygen therapy influenced the presence of ROP, with prevalence in moderate preterm newborns. The adoption of ophthalmologic screening for ROP detection, with background examinations of the eyes in the NICU contributed to the early treatment and prevention of severe visual impairment and blindness caused by ROP. Thus, nurses are fundamentally important, from the prevention, the diagnosis until the course of the treatment and for discharge counselling.